Design and experiment of intelligent sorting and transplanting system for healthy vegetable seedlings - Li, Mingyong; Jin, Xin; Ji, Jiangtao; Li, Pengge; Du, Xinwu (International Journal of Agricultural and Biological Engineering, 2021)
Healthy vegetable seedlings are surviving seedlings with good biological characteristics. Selective planting of healthy seedlings in the mechanized transplanting process can effectively avoid the reduction in yield caused by missed planting. Aiming at the current transplanting machinery that cannot achieve the selective planting of healthy seedlings, a healthy seedling intelligent sorting and transplanting system was proposed. The system consisted of a seedling delivery mechanism, sorting mechanism, photoelectric sensor, image sensor, PLC control system, and computer control system. It can realize automatic transmission of seedling trays, automatically identify the information of healthy seedlings in the trays and selectively transplant them. Also it can reduce the missed planting rate caused by the poor quality of plug seedlings after planting and the lack of seedlings in the hole. A sorting test of plug seedlings was carried out for the age-appropriate pepper plug seedlings cultivated in the factory. The results showed that the system had an average recognition accuracy rate of 89.14% and an average sorting success rate of 93.20% in the process of sorting suitable age pepper plug seedlings. The whole system can identify, sort and transplant the plug seedlings of appropriate age according to healthy information, and effectively avoid missing planting. This research can provide technical support for the intelligent upgrade of transplanting equipment. Keywords: intelligent agriculture, sorting and transplanting system, healthy vegetable seedling, design, experiment, image, sensor DOI: 10.25165/j.ijabe.20211404.6169 Citation: Li M Y, Jin X, Ji J T, Li P G, Du X W. Design and experiment of intelligent sorting and transplanting system for healthy vegetable seedlings. Int J Agric & Biol Eng, 2021; 14(4): 208–216.